2018
DOI: 10.1177/0091026018783022
|View full text |Cite
|
Sign up to set email alerts
|

The Nonprofit Career Ladder: Exploring Career Paths as Leadership Development for Future Nonprofit Executives

Abstract: Pending leadership transitions in the nonprofit sector present a timely need to understand the career path to the executive position, but very few studies on nonprofit career paths have been conducted. A systematic study would help make sense of the existing leadership pipeline to the executive office and offer promising insights that contribute to theory building in the sector. This study investigates the career paths of a national random sample of nonprofit executives serving health and human service nonprof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 36 publications
2
31
2
2
Order By: Relevance
“…Organizational culture was considered the second most important factor in successful executive succession planning, which was also supported by previous studies (Gothard & Austin, 2013; Mehrtak et al, 2017; Mugo et al, 2015). The third factor was leadership development opportunities, consistent with studies that found that leadership development, as a component of executive succession planning, leads to employee satisfaction and enhances organizational performance (Manning et al, 2015; Stewart & Kuenzi, 2018; Yadav & Dixit, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…Organizational culture was considered the second most important factor in successful executive succession planning, which was also supported by previous studies (Gothard & Austin, 2013; Mehrtak et al, 2017; Mugo et al, 2015). The third factor was leadership development opportunities, consistent with studies that found that leadership development, as a component of executive succession planning, leads to employee satisfaction and enhances organizational performance (Manning et al, 2015; Stewart & Kuenzi, 2018; Yadav & Dixit, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…From this, extrinsic and intrinsic motivations both fuel sector choice and commitment (for a compilation of this research, refer to . Findings from studies of nonprofit workers suggest that many individuals currently working in the sector seek out these positions intentionally (Stewart & Kuenzi, 2018) with a strong desire to remain in these positions regardless of other mitigating factors or opportunities (Walk et al, 2020). However, evidence documents commitment can change over time (citation redacted for peer review), and we are concerned that nonprofit workers may encounter factors, such as prolonged uncertainty, COVID-19 related trauma, even concomitant concerns from the pandemic coupled with widespread social unrest that distract them from their commitment, prompting them to leave the sector for other career prospects.…”
Section: Nonprofit Sector Commitmentmentioning
confidence: 99%
“…Jäger et al (2013Jäger et al ( , p. 1028) applied concept of "career capital" to a sample of nonprofit executives to appreciate the temporal elements of an executive's career that accumulate from "past experiences, present actions, and future expectations." A study by Stewart and Kuenzi (2018) documented these 'past experiences' that comprised a sample of health and human service executives' career paths, making note of their credentials and experience. Yet, insufficient evidence still exists about what factors matter in this input-output relationship towards promotion to the top.…”
Section: Nonprofit Careersmentioning
confidence: 99%
“…Higher education, as a credentialing source, has been documented as an explanatory factor of career advancement (Becker, 2009). Yet, the widespread prevalence of undergraduate education among nonprofit professionals (Norris-Tirrell et al, 2018;Stewart & Kuenzi, 2018;Suarez, 2010) indicates an undergraduate degree alone may no longer be sufficient.…”
Section: Credentialsmentioning
confidence: 99%
See 1 more Smart Citation